Choice of parents for earliness and yield of carioca-type bean - Vale, Naine Martins do; Barili, Leiri Daiane; Oliveira, Henrique Morais de; Carneiro, José Eustáquio de Souza; Carneiro, Pedro Crescêncio Souza; Silva, Felipe Lopes da (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate promising bean lines for the selection of parents, with carioca grain-type traits, early, and with high productive potential. Thirty‑five common bean lines were evaluated in a randomized complete block design with three replicates. Four of these lines – Goiano Precoce, XAN112, Carioca1070, and Rosinha Precoce – were used to compose the group 1 of a 4×5 partial diallel, and three – RP1, VC15 e VC33, of normal cycle and carioca grain type with high yield potential – were used to compose the group 2 of the diallel, together with the cultivars BRSMG Mandrepérola and BRS Estilo. Twenty hybrids were obtained, which were evaluated with their parents in the dry season of 2013, in Coimbra and Viçosa, in the state of Minas Gerais, Brazil, in a randomized complete block design with three replicates. Goiano Precoce line stood out for earliness with negative and significant values of general combining ability (GCA), in Viçosa (‑3.15) and Coimbra (‑3.44). RP1 line stood out for grain yield with positive and significant GCA values, in Viçosa (115) and Coimbra (260). Based on the GCA, Goiano Precoce is a promising line to be used as a parent for earliness, and RP1 for grain yield increase.
Keywords: Phaseolus vulgaris; diallel analysis; partial diallel